Comparison of bovine and porcine skin gelatin based on amino acid composition, polypeptide pattern and gel strength - Raja Nhari, Raja Mohd Hafidz; Che Man, Yaakob; Anuar, N. (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
The ability to compare bovine skin gelatin (BSG) and porcine skin gelatin (PSG) based on their amino acid content, polypeptide pattern and Bloom strength were investigated. Amino acid composition analysis of the two types of gelatin showed that the content of glycine, proline and arginine in PSG were higher than BSG. In the other hand, the Bloom strength of PSG and BSG was determined in different pH value ranging from pH 3 to pH 10. Within this pH range, PSG confer higher Bloom strength as compared to BSG. Both gelatins have the highest Bloom strength at pH 9 while the lowest Bloom strength of BSG and PSG was at pH 3 and pH 5 respectively. However, there is no difference of polypeptide pattern between PSG and BSG as both of them consists of α and β chains.